(3TQM CQLhRI GHf SjfG aj GdWHs - (3eMeO Hf CMeO Hf eMeO Hf QTO GdbQWHj GdCfOdSj, CHh GdhdjO (B((3GdMajO(B)(3,J (B595 (3g` s; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg GdefYe HMjGI GdfaS hUMI GdCLSGe , hGdTGai ef GdCOhGA GdeYVdI hGdCSbGe hEfg PcQ HGdeLdS GdYGdi eLdS GdSjO CHj GdQHjY GHf CHj eMeO GdCQLhRI GdefShHI Edi GHf SjfG ai GdWH hCfgG eMjWI HLejY cdjGJg s
(3BNQgG (B:s
(3GdYde hGdMQU Ydi GdMb heMHI ai Cgdg ai GdBNQI HaVdg hQMeJg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B150s
(3GfXQ TQM efXehI GHf SjfG GdWH Qbe (B" 562"s
(3fSNI KGdKIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
Keywords: (3GdWHs